Perancangan Pembelajaran Bangun Ruang 3 Dimensi Berbasis Android - Imam Abdurrahman; Ucuk Darusalam; Benrahman Benrahman (STMIK Budi Darma, 2020)
Teaching aids for learning to Build Space now still depend on the old way, namely by still using 2-Dimensional media. Teachers such as Teachers still have difficulty making visual tools to learn the material of Building 3 Dimensions. And students still find it difficult to learn and explore the material to Build Space delivered by the teaching staff, with its limitations and lack of visual tools they can only imagine what the shape of the Space Build is like. With that, the author tries to make interactive learning applications so that geometric models such as cubes, tubes, cones, pyramids and balls can foster interest in learning mathematics at elementary school level by utilizing Augmented Reality (AR) technology, which is technology that merge two-dimensional or three-dimensional virtual objects into a real environment and then project these virtual objects in real time. One of the materials in learning mathematics for fifth grade elementary school students is Build Space. If you pay attention to the average age of elementary school students in class V is at the age of 10-11 years. The author obtained the final results of the study in the form of learning to Build 3-Dimensional Space with the Virtual Button method and test results from Smartphone Xiaomi Redmi 4 devices with a minimum distance of ± 15cm and a maximum of ± 81cm. Testing the response speed <1 second, the Xiaomi Redmi 4 Smartphone shows better results than other smartphones.